Neutrophil microvesicles drive atherosclerosis by delivering miR-155 to atheroprone endothelium - Gomez, I; Ward, B; Souilhol, C; Recarti, C; Ariaans, M; Johnston, J; Burnett, A; Mahmoud, M; Luong, L; West, L; Long, M; Parry, S; et al. (Springer Nature, 2020)
Neutrophils are implicated in the pathogenesis of atherosclerosis but are seldom detected in atherosclerotic plaques. We investigated whether neutrophil-derived microvesicles may influence arterial pathophysiology. Here we report that levels of circulating neutrophil microvesicles are enhanced by exposure to a high fat diet, a known risk factor for atherosclerosis. Neutrophil microvesicles accumulate at disease-prone regions of arteries exposed to disturbed flow patterns, and promote vascular inflammation and atherosclerosis in a murine model. Using cultured endothelial cells exposed to disturbed flow, we demonstrate that neutrophil microvesicles promote inflammatory gene expression by delivering miR-155, enhancing NF-κB activation. Similarly, neutrophil microvesicles increase miR-155 and enhance NF-κB at disease-prone sites of disturbed flow in vivo. Enhancement of atherosclerotic plaque formation and increase in macrophage content by neutrophil microvesicles is dependent on miR-155. We conclude that neutrophils contribute to vascular inflammation and atherogenesis through delivery of microvesicles carrying miR-155 to disease-prone regions.